(3GdJdhK GdHjFj (B:s (3GdghGA, GdeGA hGdZPGA (B/s - (3NfaQ, YGjO QGVjs ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2010)
(3GdHjFI YfGUQgG h eQGMdgG , eQGMd GdJdhK , GdedhKGJ (B: (3MGdGdJgG h eUOQgG ,GdJdhK GdGTYGYj , JbOjQ JdhK GdghGA , GdJMce h GdSjWQI aj edhKGJ GdghGA , GdJdhK GdeGFj h WQb LeY YjfGJ GdeGA , GdJMdjd GdajRjGFj `` GdcjejGFj ddejGg , GdcGFfGJ GdMjI h GdGMjGA GdObjb aj GdeGA , GdcJdI GdMjhjI , OQGSI GdGfJGLjI GdGhdjI , GdJdhK GdZPGFj (B.s
(3eQGLY U(B.365s
Keywords: (3GdHjFIs; (3GdJdhKs; (3GdJdhK GdHjFjs; (3GdJdhK GdUfGYjs